2008
DOI: 10.1007/s10347-008-0134-8
|View full text |Cite
|
Sign up to set email alerts
|

Facies characteristics and diversity in carbonate eolianites

Abstract: Carbonate eolian dunes can form huge sand bodies along the coasts but are seldom described in the pre- Quaternary record. The study of more than 600 thin-sections collected in present-day, Holocene and Pleistocene dunes from Sardinia, Crete, Cyprus, Tunisia, Morocco, Australia and Baja California conWrms that these deposits can be easily misinterpreted as shallow marine at core or thin-section scale. The classical eolian criteria (Wne-grained and well-sorted sands) are exceptional in carbonate dunes because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 24 publications
3
41
0
Order By: Relevance
“…Pleistocene/Holocene deposits in San Salvador experienced an intense reworking of previously deposited marine carbonates forming aeolianites (Caputo, ; Carew & Mylroie, ; Hagey & Mylroie, ; White, ). Among the aeolian deposits, carbonate aeolianites are peculiar because traditional recognition criteria are rare (Frébourg et al ., ). Studies on modern coastal environments highlight that vadose or pedogenic imprints are common in carbonate aeolianites (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleistocene/Holocene deposits in San Salvador experienced an intense reworking of previously deposited marine carbonates forming aeolianites (Caputo, ; Carew & Mylroie, ; Hagey & Mylroie, ; White, ). Among the aeolian deposits, carbonate aeolianites are peculiar because traditional recognition criteria are rare (Frébourg et al ., ). Studies on modern coastal environments highlight that vadose or pedogenic imprints are common in carbonate aeolianites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on modern coastal environments highlight that vadose or pedogenic imprints are common in carbonate aeolianites (e.g. Flügel, ; Frébourg et al ., ). In the Cayo Coco lagoonal network, the substrate (F1) only crops out several centimetres to decimetres on the surface; thus, a 3D geometric study of these deposits is not possible, because they are covered primarily by mangroves and recent lagoonal sedimentation.…”
Section: Discussionmentioning
confidence: 99%
“…Eolianites can occur within transgressive or regressive parts of sequences or both (Carew and Mylroie 2001;Frébourg et al 2008). stated that eolinates overlying subaerial exposure surfaces are interpreted to be deposited during transgressions.…”
Section: Quartz-peloidal Grainstonementioning
confidence: 97%
“…A number of previous publications showed that these rocks are, to a large extent, of Quaternary age with a global distribution (Fairbridge and Johnson, 1978;Thomas, 1997) and were formed during both low and high stands of the global sea level. From the sedimentological point of view, moderate-to-hard cementation, cross-bedding (Frébourg et al, 2008), and rhizolith content as organosedimentary components (Klappa, 1980) are some common properties of those eolian occurrences. Based on the preceding attributes, eolianites provide sound evidence of multifarious dune generation in coastal environments (Brooke, 2001).…”
Section: Introductionmentioning
confidence: 99%